Estimation of logit models for different types of freight in urban freight transport: a new discrete choice model group for Istanbul - Aksoy, Berna; Gursoy, Mustafa (CANADIAN SCIENCE PUBLISHING, 2025)
Freight transportation plays a significant role in urban transport and contributes substantially to environmental issues due to the use of heavy vehicles. However, compared to passenger transport, decision-makers often overlook the impact of freight transport despite its contribution to congestion. The leading factors influencing the selection of freight vehicles include cost, freight size, and packaging characteristics. However, existing transportation studies mainly examine freight vehicle preferences at a general level, needing a comprehensive understanding of freight transportation. To address this gap, through the framework we propose in this study, we present a discrete modeling-based methodology to identify the factors that determine freight vehicle preferences for shipping and sender firms with the ultimate motivation of exploring the significant factors to ensure more efficient freight transportation. The presented framework is tested through a real-world case study conducted in Istanbul, Turkey, utilizing field surveys conducted by the Municipality within the context of a newly developed Logistics Master Plan for the city. Two of the four freight model structures created gave outputs highly accepted in the literature. Interestingly, the findings deviated from the existing literature, revealing that the choice of freight vehicles is influenced by different packaging variables depending on the freight type being transported.
Keywords: discrete choice analysis; mode choice; logit model; freight transportation; GIS; freight modeling; Engineering